Esophageal Reconstruction - Strutynska-Karpinska, Marta; Grabowski, Krzysztof (IntechOpen, 2012)
The present book, based on knowledge and great experience of the authors includes a wide study problem of reconstructive esophageal surgery with use of pedicled intestinal segments, in detail discusses vascular anatomy of intestines, difficulties and threats which may occur intraoperatively, presents diagnostic procedures and treatment standards of early postoperative complications as well as late complications that lead to diseases of esophageal substitutes. Authors also discuss a function of various substitutive esophagi. The book complements professional literature in the field of esophageal surgery.